The Potential of Kelakai Leaf Peat Plants (Stenochlaena Palus-tris Bedd) as Sunscreen Based on Sun Protecting Factor (SPF) Values In Vitro - Adelia, Kadek Ayu Cintya; Kurniati, Ety; Kalalinggi, Septaria Yolan (Jurnal Penelitian Sains, 2025)
Kelakai (Stenochlaena palustris (Burm F.) Bedd) is a type of fern that grows in peat swamp areas or commonly called wetlands. Kelakai leaves contain secondary metabolites, namely flavonoids, which are effective as antioxidants and counteract free radicals. The purpose of this study was to determine whether the extract of kelakai leaves (Stenochlaena palustris (Burm.F.) Bedd) has sunscreen protection activity.UV radiation or known as ultraviolet consists of 2 types, namely: UV-A and UV-B, the letter A in UV-A means "Aging" with a wavelength of 320-400 nm can penetrate the dermis which causes pigmentation, and the letter B in UV-B means "Burning" with a wavelength of 290-320 nm and can penetrate the outermost layer of the skin (epidermis) whose effects can be seen directly in the form of erythema. The SPF value indicates how many times a person's skin protection is doubled so that it is safe under the sun without experiencing erythema, the higher the SPF value of a sunscreen, the better its protection activity. Based on the SPF value data obtained, it shows that the ethanol extract of kelakai leaves can function as an active ingredient in sunscreen because it is proven to have quite high activity and SPF value from minimal protection to ultra protection.